Case reportGranulomatous inflammation of dura mater – a rare side effect after application of hemostatic and insulation materials in case of two-stage operation of huge meningioma - Andrychowski, Jarosław; Czernicki, Zbigniew; Taraszewska, Anna; Frontczak-Baniewicz, Małgorzata; Przytuła, Ewa; Zębala, Marta (Folia Neuropathologica, 2012)
Haemostatic and isolating materials may cause local reactions as a foreign body. The case presented here of intracranial granulomatous lesion pertains to a patient operated in two stages due to a huge meningioma. During the first operation the tumour was partially removed. Because of persistent intraoperative haemorrhage haemostatic flakes of Oxycel and Spongostan were applied locally. In order to cover the lack of the dura, an insulation material – Tachosil was used. Histological examination of the tumour specimens confirmed the preoperative diagnosis of benign meningioma, mainly of the angiomatous subtype. The second stage of operation was performed after 3 months and the meningioma was completely removed, as well as dura mater and meningioma attachment with its oncological margin. The resected dura mater was thickened and histologically showed intensive granulomatous infiltrations and foreign body reactions most likely to Oxycel. Clinically no local and general infection and improper healing was observed after the first and the second treatment stage, but an allergic skin lesions and increased eosinophils in peripheral blood smear were noted. It was stated that systemic allergic reaction and granulomatous inflammation of dura mater were an uncommon response to the applied haemostatics and/or insulation material used during the first operation. This report show that haemostatic and isolating agents, generally used in neurosurgical procedure, may rarely cause local granulomatous processes considered as delayed hypersensitivity and the foreign body reactions. Therefore, they may hinder morphological assessment of the tissues during re-exploration and must be differentiate with the other infectious and non-infectious granulomatous processes.